Aconite Poisoning: From Crisis to Healing - Barsha Baral; Arjun Kandel; Sajjad Ahmed Khan; Pratik Raj Regmi; Saurav Jha; Rajat Shah (Clinical Case Reports)
ABSTRACT Early recognition and prompt intervention are crucial in managing aconite poisoning. Rapid treatment with intravenous magnesium sulfate and amiodarone can stabilize severe cardiac arrhythmias. Vigilant monitoring and tailored therapeutic strategies enhance recovery and improve patient outcomes in acute poisoning cases.